Food safety standards, compliance and European Union's rejection of African exports: The role of domestic factors - Fatima Olanike Kareem; Bernhard Brümmer; Immaculada Martinez-Zarzoso (Georg-August-Universität Göttingen, Research Training Group (RTG) 1666 - GlobalFood, 2015)
This paper investigates the causes of rejections of African exports at the EU border as a barrier in accessing EU markets. Our results indicate that natural geographical hurdle, poor trade-related infrastructure, inefficient border procedure and a lack of technical personnel increase the incidences of rejection at the EU border and add to Africa's challenges in accessing EU markets. In addition, in line with the growing literature, this study finds empirical support for the proposition that institutions, infrastructure and logistic quality matter for increased market penetration and continuous integration into the global trading system. Thus, the barrier created by EU rejection of Africa's exports can be addressed through the strengthening of African's institutions and trade facilitation measures particularly her custom and border management including transit regimes.
Keywords: F13; F14; L15; O17; C33; 330; Non-Tariff Barrier; Export Rejections; Institution; Trade Procedures; Africa; European Union